Questioning Fiqh Muamalah of Toleration: Religious Spatial Segregation in the Urban Area of Yogyakarta - Nur Quma Laila; Irwan Abdullah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2022)
Yogyakarta, despite being declared as the city of tolerance, shows religious discrimination manifested in religious spatial segregation. Discrimination is contrary to divine norms that protect the rights of each party in mu’amalah. The objective of this study is to explain that religious spatial segregation reflects intolerance in the urban community of Yogyakarta. This study relies on data collection through a qualitative approach which includes observation, interviews, and literature review with descriptive analysis considering fiqh muamalah principles on the interfaith relationships. The results suggest that religious spatial segregation may lead to the emergence of intolerant and discriminative acts in the forms of; (1) the presence of housing associated with a certain religious identity as a manifestation of identity labeling in social recruitment (exclusivism); (2) the practice of land trading (property right) only with people from the same faith; and (3) segregation in social acceptance (social exclusion) as seen in boarding houses with a certain religious label. This study concludes that religious spatial segregation has shallowed the relations between community groups and thus raising the potential of discriminative and intolerant acts in the urban area of Yogyakarta. This study suggests that there is a need for a policy to regulate space as a common one, hence spatial exclusivism for a certain religion can be eliminated.